2011
DOI: 10.1093/infdis/jir549
|View full text |Cite
|
Sign up to set email alerts
|

Virus Infection Stages and Distinct Th1 or Th17/Th22 T-Cell Responses in Malaria/SHIV Coinfection Correlate with Different Outcomes of Disease

Abstract: These novel findings suggest that virus infection status and selected Th1 or Th17/Th22 responses after malaria/AIDS-virus coinfection correlate with distinct outcomes of virus infection and malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Since mouse IFNγ and perforin are needed for anti-TB immunity [23], [24], [25], [26] and human granulysin kills Mtb [4], we examined if these anti-TB cytokines could be produced by Picostim-expanded Vγ2Vδ2 T cells in the pulmonary compartment. We employed both the conventional intracellular cytokine staining(ICS) upon in vitro antigen stimulation and the modified direct ICS assay without in vitro antigen stimulation since the direct ICS assay had been demonstrated to be useful for measuring T effector cells that were close to the in vivo setting during infections [22], [27], [28], [29], [30]. We found that appreciable numbers of Vγ2Vδ2 T cells in the pulmonary compartment were able to re-recognize HMBPP phosphoantigen and produce IFNγ over time after the Picostim/IL-2 administration(Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since mouse IFNγ and perforin are needed for anti-TB immunity [23], [24], [25], [26] and human granulysin kills Mtb [4], we examined if these anti-TB cytokines could be produced by Picostim-expanded Vγ2Vδ2 T cells in the pulmonary compartment. We employed both the conventional intracellular cytokine staining(ICS) upon in vitro antigen stimulation and the modified direct ICS assay without in vitro antigen stimulation since the direct ICS assay had been demonstrated to be useful for measuring T effector cells that were close to the in vivo setting during infections [22], [27], [28], [29], [30]. We found that appreciable numbers of Vγ2Vδ2 T cells in the pulmonary compartment were able to re-recognize HMBPP phosphoantigen and produce IFNγ over time after the Picostim/IL-2 administration(Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Direct ICS was adapted from the conventional ICS protocol, and the major modification was that PBMC or BAL cells were directly measured by ICS for intracellular cytokines without prior in vitro Ag stimulation as we recently described [17], [27], [28], [29], [44]. Direct ICS approach was characterized and validated extensively in vitro and in vivo conditions as we previously reported [17], [22], [27], [28], [29], [30].…”
Section: Methodsmentioning
confidence: 99%
“…This was done exactly the same as we previously described (36, 38, 45). Briefly, 10 6 PBMC, 10 6 or 3–5 ×10 5 lymphocytes (depending on availability) from BAL fluid or lung tissues were used in each reaction (round bottom 96-well plate) to measure T cells and CD3-negative lymphocytes that could constitutively produce IFNγ, TNFα, IL-17, IL-22, IL-4, and perforin without Ag stimulation in vitro .…”
Section: Methodsmentioning
confidence: 99%
“…As another control setting, PBL were collected weekly or bi-weekly for up to 3 months from 2 uninfected healthy macaques and 4 SHIV-infected macaques, and assessed for de novo production of IFN-γ, IL-17, and IL-22 over time using the direct ICS approach without Ag stimulation in vitro. T cells from these controls gave rise to no or very low levels of cytokines stained by this direct ICS methods (36, 38, 45). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation